2023
DOI: 10.3390/life13081695
|View full text |Cite
|
Sign up to set email alerts
|

Cultivable Endophyte Resources in Medicinal Plants and Effects on Hosts

Abstract: With the increasing demand for medicinal plants and the increasing shortage of resources, improving the quality and yield of medicinal plants and making more effective use of medicinal plants has become an urgent problem to be solved. During the growth of medicinal plants, various adversities can lead to nutrient loss and yield decline. Using traditional chemical pesticides to control the stress resistance of plants will cause serious pollution to the environment and even endanger human health. Therefore, it i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 124 publications
(169 reference statements)
0
1
0
Order By: Relevance
“…For instance, Strobel and Daisy highlighted in their seminal paper the vast potential of endophytes as producers of novel bioactive metabolites that could have applications in medicine, agriculture, and industry [ 44 ]. Additionally, Wang et al demonstrated that endophytic fungi from medicinal plants may produce a plethora of novel compounds with antimicrobial, anticancer, and other health-related benefits [ 45 ]. Therefore, the focused exploration of endophytic fungi within medicinal plants not only helps in conserving these plants by uncovering alternative sources of therapeutic compounds but also propels the discovery of new drugs.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Strobel and Daisy highlighted in their seminal paper the vast potential of endophytes as producers of novel bioactive metabolites that could have applications in medicine, agriculture, and industry [ 44 ]. Additionally, Wang et al demonstrated that endophytic fungi from medicinal plants may produce a plethora of novel compounds with antimicrobial, anticancer, and other health-related benefits [ 45 ]. Therefore, the focused exploration of endophytic fungi within medicinal plants not only helps in conserving these plants by uncovering alternative sources of therapeutic compounds but also propels the discovery of new drugs.…”
Section: Discussionmentioning
confidence: 99%